New records of the striped lizard Kentropyx paulensis from Sao Paulo, Brazil - Queiroz, Vinicius Oliveira [UNESP]; Moya, Guilherme Marson [UNESP]; Morais, Drausio Honorio; Bronzatto Medolago, Cesar Augusto; Pagotto, Thais; Prist, Paula; Abra, Fernanda Delborgo; Maffei, Fabio [UNESP] (Univ Federal Campina Grande, 2022)
The endemic Cerrado teiid lizard Kentropyx paulensis is classified in the Endangered and Vulnerable categories by the lists of the states of Sao Paulo and Minas Gerais, respectively, and is therefore considered threatened. Thus, this work aimed to compile records of K. paulensis obtained in several works carried out in the Planalto Ocidental Paulista, which occupies almost half of the total area of the State of Sao Paulo, Southeastern Brazil. Records were produced in seven municipalities (Anhembi, Assis, Castilho, Jau, Piracicaba, Quata and Santa Barbara d'Oeste) in the hot and rainy season (December to March) in vegetation types ranging from natural environments such as Cerradao and Semideciduous Seasonal Forest to anthropized environments as reforestation and pastures of Urochloa sp. The intense process of changing the landscape that the Planalto Ocidental Paulista went through in the last century, because of the economic model that the state adopted, may have collaborated to reduce the viable areas for the maintenance of these populations. These new records indicate that the occurrence of the species may be broader, as a result of adaptations to recent conversion of cover natural that occurred in the State of Sao Paulo.
Keywords: Anthropic; brazilian savannah; Teiidae